The Usefullness of Green Coconut Water Supplementation in Overcoming The Toxic Effect of Mercury Chloride in The Blood and Blood Profile (Study in Sprague Dewly Rats) - Abdulrzag Ehmeeda; Tri Nur Kristina; Ari Suwondo; Henna Rya Sunoko (Biosaintifika: Journal of Biology & Biology Education)
When people are exposed to mercury chloride, it can produce a variety of health effects in the blood and liver. Coconut water contains Zn, Fe, Vit. C, Vit B11, Vit. B6, and Se to reduce mercury chloride level in the blood and improve blood profile. Aim of this study was to analysis the effect of green coconut water supplementation in overcoming the toxic effect of Hg chloride in the blood of Sprague dawley rats exposed to Hg chloride. Samples were randomly about 36 animals rats exposed to HgCl2 through forced feeding by 20 mg/kgBW sondage perday for 14 days, which divided into control group, and intervention groups were given fresh green coconut water in each by 6, 8, and 10 mL/kgBW for intervention 7 and 17 days. The result of this study showed that there is a significant effect and the decrease in mercury levels in the blood. There is no significant affect on the hemoglobin level, hematocrit level and platelet count with the treatment of green coconut water in the rats with exposure Hg. New findings/significance of contribution were the effectiveness of green coconut water to reduce Hg level in blood and improve blood profile.